Аналіз складних мереж на прикладі соціальної мережі в Інтернет - Головін, Ю.О.; Головін, А.Ю. (Збірник наукових праць Інституту проблем моделювання в енергетиці ім.Г.Є.Пухова НАН України, 2009)
Today Social Network Analysis (SNA) is rather actual research direction. A new
branch of the discrete mathematics was developed. It is called complex network
theory. Besides topology analysis, it explores characteristics of each node and of the entire network. This article covers the exploration of one of the biggest social network in Internet.